2022
DOI: 10.4236/jacen.2022.113014
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Steel Slag on Soil Fertility and Plant Growth

Abstract: The effective utilization of steel slag, a byproduct produced in large quantities from the steel refining process, is an important issue. Because steel slag contains abundant mineral components, the effects of steel slag on soil bacterial biomass and plant mineral uptake were analyzed in this study. The soil pH increased in proportion to the amount of steel slag added. A lower concentration (0.2% to 1%) of steel slag addition did not change the bacterial biomass. However, a higher concentration of steel slag (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…This could be probably due to the excess of mineral elements present in high amount in the D2 concentration of slag (20 g slag/ kg soil) that could become toxic to the development of wheat plants (Wang & Cai, 2006). Other researches showed a significant increase in growth and biomass accumulation for low rates of slag, while increasing application rates of slag did not improve the growth (Cai et Islam et al (2022) showed that the high rates of slag application in the soil led to a huge accumulation of Fe and decreased bacterial biomass in the soil, which could create a poor assimilation of nutrients and be a source of inhibition of plant growth. In contrast, application of steel slag to agricultural land can provide potential benefits for soils in the form of increased availability of Ca and P (Yang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could be probably due to the excess of mineral elements present in high amount in the D2 concentration of slag (20 g slag/ kg soil) that could become toxic to the development of wheat plants (Wang & Cai, 2006). Other researches showed a significant increase in growth and biomass accumulation for low rates of slag, while increasing application rates of slag did not improve the growth (Cai et Islam et al (2022) showed that the high rates of slag application in the soil led to a huge accumulation of Fe and decreased bacterial biomass in the soil, which could create a poor assimilation of nutrients and be a source of inhibition of plant growth. In contrast, application of steel slag to agricultural land can provide potential benefits for soils in the form of increased availability of Ca and P (Yang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…(2006) and Das et al (2019) have assessed the agronomic utility of steel slag as a fertilizer or as a liming material. Different types of steel slag had a good effect on crop output, but the effect varied depending on the plant species, type of soil, or climate (Das et al, 2020;Islam et al, 2022). Iron and steel slags were used in the pot experiments, which showed an increase in corn dry matter yield and Fe uptake for moderate rates of slag without having any negative phytotoxic consequences (Wang & Cai, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Chemical fertilizers have been extensively used in agricultural practices throughout the 20 th century to achieve high crop yields [1]. Inorganic forms of chemical fertilizers, particularly those containing nitrogen, phosphorus, and potassium, can be directly applied to the soil and immediately absorbed by plants.…”
Section: Introductionmentioning
confidence: 99%
“…The efficient disposal of steel slag has always been a challenge faced by the steel industry. In recent decades, steel slag has been applied in many fields, mainly involving wastewater purification [17], sewage sludge stabilization [18,19], carbon sequestration [20,21], agriculture utilization [22], cement and concrete production [23,24], road construction [25,26], etc. Recycling steel slag in road construction is very attractive as the high consumption of materials in road construction can accelerate the disposal of solid waste.…”
Section: Introductionmentioning
confidence: 99%